LEGAL STATUS OF ARMED CRIMINAL GROUPS IN THE PERSPECTIVE OF INTERNATIONAL HUMANITARIAN LAW - Asroflie, Moch Farrel; Darmoko, Murry (jfpublisher, 2023)
The shooting case in Nduga Papua killed dozens of civilians. On December 1st and 2nd 2018, the civilians who working on Trans Papua bridge construction project become the victim to weapons by Free Papua Organization Armed Criminal Group (KKB-OPM). The purpose of this research is to answer the problems regarding armed conflict in Nduga Papua. The research method used in making this scientific journal is to use normative juridical methods that examines legal issues as well as provides a prescription regarding the examined case. This research will indicates the influence of power character with the shift based on Pancasila. Intially, Indonesia’s raison d’être was to liberate the colonized peoples from imperialism. Unfortunately, it reversed from that spirit that become into an imperialistic spirit in its implementation. By returning to its original spirit, Papua must be maintained as part of the sovereignty of Unitary State of Republic of Indonesia. The most prominent national security issues are terrorism, transnational security threats, and communal conflicts. Several preventive, repressive, and restorative legal solutions are necessary in order to confront the armed criminal groups and ensure their responsibility for the crimes committed.